Factors influencing the prevalence of cervical cancer screening in Malaysia: a nationwide survey - Yee Mang Chan; Muhd Zulfadli Hafiz Ismail; Wan-Fei Khaw (BMC Women's Health, 2023)
Abstract Background In 2020, cervical cancer ranked fourth in terms of both frequency of diagnosis and the leading cause of cancer-related deaths among women globally. Among Malaysian women, it was the third most prevalent form of cancer. Published data on nationally representative cervical cancer screening in Malaysia have been limited. Therefore, this study aimed to determine the prevalence of receiving a Pap smear test in the past three years, its relationship with socio-demographic factors and physical activity. Methods Using a subset of survey data from the National Health and Morbidity Survey (NHMS) 2019, a secondary data analysis was performed. Trained research assistants collected data through face-to-face method using a mobile tablet questionnaire system application. Logistic regression analysis was performed to examine the relationship between sociodemographic factors, physical activity, and cervical cancer screening. The analyses were conducted using STATA version 14 (Stata Corp, College Station, Texas, USA), accounting for sample weighs and complex sampling design. Results The analysis included 5,650 female respondents, representing an estimated 10.3 million Malaysian female adults aged 18 and above. Overall, 35.2% (95%CI 33.2, 37.4) respondents had a Pap smear test within the past three years. Respondents who were physically active were 1.41 times more likely to have a Pap smear test. Similarly, respondents aged 35–59 (OR 1.84; 95%CI 1.46, 2.34) and those living in rural localities (OR 1.38; 95%CI 1.13, 1.70) had higher odds of receiving a Pap smear test. Compared to married respondents, single respondents (OR 0.04; 95%CI 0.02, 0.07) and widowed/divorcee respondents (OR 0.72; 95%CI 0.56, 0.82) were less likely to receive a Pap smear test. Educated respondents were more likely to have had a Pap smear test. Conclusions The overall prevalence of cervical cancer screening in Malaysia remains low (35.2%). Efforts should be made to strengthen health promotion programs and policies in increasing awareness on the significance of cervical cancer screening. These initiatives should specifically target younger women, single women, and widowed/divorced individuals. The higher cervical screening uptake among rural women should be studied further, and the enabling factors in the rural setup should be emulated in urban areas whenever possible.